2017
DOI: 10.1080/15548627.2017.1353841
|View full text |Cite
|
Sign up to set email alerts
|

Mir505–3p regulates axonal development via inhibiting the autophagy pathway by targeting Atg12

Abstract: In addition to the canonical role in protein homeostasis, autophagy has recently been found to be involved in axonal dystrophy and neurodegeneration. Whether autophagy may also be involved in neural development remains largely unclear. Here we report that Mir505-3p is a crucial regulator for axonal elongation and branching in vitro and in vivo, through modulating autophagy in neurons. We identify that the key target gene of Mir505-3p in neurons is Atg12, encoding ATG12 (autophagy-related 12) which is an essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
13
1
Order By: Relevance
“…As already mentioned, this process requires very dynamic structural plasticity, and our data suggest that such plasticity would be achieved only with the involvement of autophagy. Our data are in contrast with those of Ban et al (Ban et al, 2013) and Yang et al (Yang et al, 2017), where autophagy seemed to negatively regulate axon growth in cortical neurons. However, this difference might be explained by neuronal type-specific differences (dopaminergic neurons vs. cortical neurons) and by the experimental approach.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, this process requires very dynamic structural plasticity, and our data suggest that such plasticity would be achieved only with the involvement of autophagy. Our data are in contrast with those of Ban et al (Ban et al, 2013) and Yang et al (Yang et al, 2017), where autophagy seemed to negatively regulate axon growth in cortical neurons. However, this difference might be explained by neuronal type-specific differences (dopaminergic neurons vs. cortical neurons) and by the experimental approach.…”
Section: Discussioncontrasting
confidence: 99%
“…Knockout embryos for Ambra1, an autophagy-related protein, display accentuated mid-hindbrain exencephaly (Fimia et al, 2007), whereas Atg7 conditional knockout (cKO) in mDA neurons leads to aberrant axonal morphology and altered dopamine release in young animals (Hernandez et al, 2012). Moreover, Alfy/WDFY3, an autophagy adaptor protein, has been shown to regulate the formation of major axonal tracts in the brain as well as in the spinal cord (Bosco et al, 2016), and microRNA Mir505-3p, which targets Atg12, a core autophagic protein, regulates axonal elongation and branching in vitro and in vivo (Yang et al, 2017). Much of this evidence, however, comes from experiments with autophagic adaptor and/or regulatory proteins, not core autophagic proteins; therefore, it cannot be excluded that some of the brain defects reported might be related to their non-autophagic roles.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that mouse cortical neurons were treated at day 4 or 5 in vitro , whereas the human neurons were differentiated for several weeks. Autophagy inhibition appears to play a role in axon development and branching in developing mouse cortical neurons 41 , 42 , whereas lysosomal content increases significantly as cultured human neurons mature 9 , 31 . Either of these observations might explain the differing susceptibility of these neurons to ambroxol.…”
Section: Discussionmentioning
confidence: 97%
“…Finding the target gene of miR-505-3p which underlies puberty onset in female mice can help to describe the regulation mechanism of this complex trait. In our previous work, we identified that one of the important functions of miR-505-3p was that it is a crucial regulator of axonal elongation and branching (through modulating autophagy in neurons) (Yang et al 2017). Atg12 is the key target gene of miR-505-3p in this process, as its protein product ATG12 (autophagy-related 12) is an essential component of the autophagy machinery during the initiation and expansion steps of autophagosome formation.…”
Section: :3mentioning
confidence: 99%